Triage strategies for COVID-19 cases : a scope review - Mazoni, Simone Roque (2022)
In the midst of the pandemic caused by the new coronavirus (SARS-CoV-2), researchers and governmental and non-governmental institutions are mobilizing to implement strategies to face cases of COVID-19. Aim: This study aimed to map the triage strategies for cases of COVID-19, with the purpose of identifying sources in the literature that make it possible to explore the understanding of the strategies in different contexts. A scope review was conducted with searches in the CINAHL Database, PubMed, LILACS and hand-search, considering studies carried out with users of health services and documents published by governmental and non-governmental institutions, between the years 2019 and 2020, resulting in 40 articles for full reading. To explore the key concept, thematic analysis was carried out at two levels: (1) triage strategies, (2) forms and experiences of triage. Five triage strategies were mapped: health services triage; digital triage by remote use of technologies; community triage; home visit triage and airport and port triage. The forms and experiences of mapped triages involved risk classification, diagnosis and definition of conducts or combined. The use of strategies with remote technological resources stands out, as well as the adaptation of existing scales with simple algorithms as a tendency.